O. Hood Phillips & Jackson : constitutional and administrative law. - Phillips, Owen Hood (Sweet & Maxwell., 2001)
This edition covers the many significant developments that have occurred since publication of the previous edition. These include the increased impact of Community Law, the revival of interest in "habeous corpus" as an alternative to judicial review, and the Scott Report and civil service changes